A política pública de creche em Manaus e a luta do movimento de mulheres por sua efetivação - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This study assumes the purpose of verifying that situation is the public policy of daycare in Manaus city, focused on serving women workers, its barriers and challenges, with particular emphasis on the figure of the feminist movement as receiver of this policy whose services are directed to children. There is a significant participation of women in the struggle for childcare in Brazil and in Manaus city in various historical moments, being integrated into the feminist movement and women to demand from the State the right daycare for working mothers. The research is guided by the critical-dialectical perspective seeking to understand the particular reality of political practice of working women within Manauense society, in a movement of social construction of public policies, particularly public policy daycare, noting their effectiveness and / or failure in Manaus city. Among the many aspects revealed it was evident the fact that there is inefficiency of public policy daycare in Manaus, having, therefore, a certain ignorance of women as protagonists of a policy as significant to the well-being of their families. There is requirement to expand this policy for working women, which is already signaled by the current Dilma Rousseff‟s government. This Government has made major investments, with the launch of the program in Brazil Affectionate May 14, 2012, the Federal Government signed an agreement with the municipalities for the construction of 1,500 kindergartens across the country, whose funding of new jobs should be the Government Federal. This process begins to take shape in our city and women have finally met the right child care for the safety of their children. Finally, we may say that the difficulties faced by women in the non-implementation of daycare for their children based on the bonds of patriarchal society that maintain gender inequalities, considering women and children as an extension of the home and relationships family.
Keywords: Gênero; Movimento Feminista; Políticas Públicas de Creche; Genre; Feminist Movement; Day care Public Policy; CIÊNCIAS SOCIAIS APLICADAS: SERVIÇO SOCIAL